The abortion divide: Exploring the role of exclusion, loss of significance and identity in the radicalization process - Knapton, Holly; Renström, Emma; Lindén, Magnus (Frontiers in Psychology, 2022)
Introduction Recently, the abortion issue has entered the spotlight in the USA, leading to potential radical actions. As the majority opinion on the abortion issue vary with state, some individuals will be in the numerical minority within their state, possibly evoking feelings of exclusion. Social exclusion can motivate a radicalization process. The aim of this paper is to explore how individuals in a numerical minority experience feelings of exclusion and significance loss and how this may drive radicalization in the context of the abortion issue. Methods A quasi-experimental design was used and 534 respondents from naturally occurring numerical minority and majority groups based on state abortion opinion participated in an online survey. Results Results showed that those in the numerical minority experienced exclusion and were more willing to engage in and endorse radical actions compared to those in the majority, regardless of position on the abortion issue. Serial mediation analysis revealed that the pathway between minority group status and engagement and endorsement of extreme actions was fully mediated by need-threat and ingroup identity. Discussion Being in the numerical minority is associated with feelings of social exclusion, which may trigger a radicalization process. The results advance our understanding of when and who is vulnerable to radicalization and that social structures that perpetuate marginalization and inequality may contribute to radicalization. Results highlight the need to continue to explore radicalization from a group-based perspective and emphasize exploring mediating factors as a pathway from social experiences to willingness to engage with radical groups.